The song of Troilus : lyric authority in the medieval book - Stillinger, Thomas C. (Middle Ages series., 1992)
The Song of Troilis traces the origins of modern authorship in the formal experimentation of medieval writers. Thomas C. Stillinger analyzes a sequence of narrative books that are in some way constructed around lyric poems: Dante's Vita Nuova, Boccaccio's Filostrato, and Chaucer's Troilus and Criseyde. The shared aim of these texts, he argues, is to imagine and achieve an unprecedented auctoritas: a "lyric authority" that combines the expressive subjectivity of courtly love poetry with the impersonal authority of Biblical commentary. Each of the three establishes its own formal and intertextual dynamics; in complex and unexpected ways, the hierarchies of Latin learning are charged with erotic force, allowing the creation of a new vernacular Book of Love. The Song of Troilus is a linked series of incisive close readings. Each chapter defines and investigates a range of philological, intertextual, and theoretical problems: in addition to explicating his three principal texts, Stillinger offers important insights into a range of medieval traditions, from Psalm commentary to Trojan historiography to Ricardian political satire. At the same time, the Song of Troilus is a sophisticated narrative of cultural change and a searching meditation on history, desire, and writing. The Song of Troilus is an original and highly readable study of three major medieval texts; it will be of compelling interest to students and scholars of medieval literature, and to all those exploring the history of authorship and the implications of literary form.